A PROFILE OF SUCCESSFUL ENGLISH LANGUAGE LEARNERS (NON-ENGLISH DEPARTMENT) - lalu isnaeni rahman (SOLID, 2018)
ABSTRACT                                                    This Journal was intended to find out what students’ learning strategies at the non-English Department at ASM MATARAM. The case study method was used to approach the research data of 15 students at secretary class. The researcher collected the data through observation, taking notes and interviewing in one semester. Then, the researcher selected, simplified and organized the raw data which refer to the research problem being investigated.The findings of the research found that, ten of the students said that they started to learn English through experiences. To their case, they learn English by making chance to find opportunity with foreigners. And also, they always listen and repeat difficult words every single day. They listen to the songs that they do like. To them, repeating words loud is an effective way to get the good pronunciation. They also have got course to add their knowledge and make an English community to make them remember the words that they have through speaking activities.Keywords: Language Learning Strategies, Successful Learner